2020
DOI: 10.3389/fbioe.2020.01027
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Loaded Lipid-Coated Hybrid Organic-Inorganic “Stealth” Nanoparticles for Cancer Therapy

Abstract: Hybrid porous nanoscale metal organic frameworks (nanoMOFs) made of iron trimesate are attracting increasing interest as drug carriers, due to their high drug loading capacity, biodegradability, and biocompatibility. NanoMOF surface modification to prevent clearance by the innate immune system remains still challenging in reason of their high porosity and biodegradable character. Herein, FDA-approved lipids and poly(ethylene glycol) (PEG)-lipid conjugates were used to engineer the surface of nanoMOFs by a rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 37 publications
2
23
0
Order By: Relevance
“…In addition, the MIL-100 MOFs consist of coordinative unsaturated metal sites (CUS) with strong Lewis acid properties produced upon thermal activation and departure of labile ligands 9,10 . The high drug payload of nanoMIL-100(Fe) has been demonstrated for various drugs 12,1312,13 , namely anticancer 2,14,15 , antibiotic 16,17 , antiretroviral 18 , and a combination of anti-inflammatory and antibiotics 19 . For example, the anticancer drug busulfan was loaded in nanoMIL-100(Fe) with a payload of 25 wt%, five and sixty times higher than its payload in polymer nanoparticles and in liposomes, respectively 2,20,21 .…”
mentioning
confidence: 99%
“…In addition, the MIL-100 MOFs consist of coordinative unsaturated metal sites (CUS) with strong Lewis acid properties produced upon thermal activation and departure of labile ligands 9,10 . The high drug payload of nanoMIL-100(Fe) has been demonstrated for various drugs 12,1312,13 , namely anticancer 2,14,15 , antibiotic 16,17 , antiretroviral 18 , and a combination of anti-inflammatory and antibiotics 19 . For example, the anticancer drug busulfan was loaded in nanoMIL-100(Fe) with a payload of 25 wt%, five and sixty times higher than its payload in polymer nanoparticles and in liposomes, respectively 2,20,21 .…”
mentioning
confidence: 99%
“…11 In recent studies, it was shown that bulkier lipids such as DOPC (1,2-dioleoyl-sn-glycero-3-phosphocholine) and PEG-DSPE (1, 2-Distearoyl-sn-glycero-3-phospho-ethanolamine-Poly(ethylene glycol)) remained anchored at the nanoMOF surface without penetrating inside the pores. 14 The porosity of the nanoMOFs was not altered by surface modifications with these FDA-approved lipids (1519 ± 50 m 2 .g -1 , 1486 ± 70 m 2 .g -1 , and 1547 ± 80 m 2 .g -1 for uncoated nanoMOFs, lipid coated nanoMOFs with and without DSPE-PEG 2000, respectively, see Figure S2). Similarly, in this study, nanoMOFs coated with FP which has bulky structure as these previously studied lipids exhibited similar BET surface area (1500 ± 70 m 2 .g -1 ), as compared to the DOPC or DSPE-PEG coated nanoMOFs.…”
Section: Resultsmentioning
confidence: 97%
“…[8,9] More recently, Food and Drug Administration (FDA)approved lipids and PEG-lipid conjugates were used to coat the surface of nanoMOFs by a rapid and convenient solvent-exchange deposition method. [10] It was shown that nanoMOF surface modification with lipids affords a better control over drug release and particle degradation. Moreover, nanoMOFs acted as "Trojan horses" carrying anticancer drugs inside cancer cells to eradicate them.…”
Section: Introductionmentioning
confidence: 99%
“…CBD induces mitochondrial dysfunction and ROS production, triggering an apoptotic cascade in glioma cells by regulating the expression of NF-κB. Li et al [56] found that the surface modification of nano-MOFs with lipids can preferably control the degradation of drugs in biological media. When loaded with anticancer medicines such as Gem-MP (gemcitabine-monophosphate), melamine iron nano-MOFs act as "Trojan horses," which carry drugs into tumor cells to destroy them.…”
Section: Research Progress Of Mof Drug Loadingmentioning
confidence: 99%